Measurement of kinematics of a flying disc using an accelerometer - Koyanagi, R.; Ohgi, Y. (Procedia Engineering, 2010)
In this study, a tri-axial accelerometer was attached to a flying disc to measure the kinematics during flight. A subject performed disc throwing. High speed video cameras were used to capture release and end points to validate boundary measurements. Results of the acceleration wave showed a sinusoidal pattern during the flight phase. According to the results of an additional verification experiment, we classified components of the acceleration wave during the flight phase to estimate the angular velocity of the disc, and validated it using high speed video cameras.